Local Government's Role in Developing Chip (Keripik) Msmes Through The Cooperative and Village Office in Bandar Lampung: A Qualitative Policy Analysis (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute a foundational pillar of Indonesia’s national economy, contributing substantially to employment generation, income distribution, and regional economic resilience. This study investigates the multidimensional role of local government in developing chip (keripik) MSMEs in Bandar Lampung City, with particular attention to the institutional mechanisms through which the Office of Cooperatives and SMEs (Dinas Koperasi dan UKM) operationalizes its developmental mandate. Situated within a qualitative research design employing descriptive-interpretive analysis, the study draws upon in-depth interviews, direct field observation, and triangulated documentation from key informants including MSME officers, enterprise owners, and employees. Findings reveal that local government functions across four institutional roles regulator, facilitator, motivator, and catalyst implemented through entrepreneurship training, zero-interest capital assistance, product marketing facilitation, and business mentoring. However, significant structural barriers persist: bureaucratic complexity in export licensing, limited digital technology adoption, low product innovation capacity, and the absence of sustained mentoring continuity. The study theorizes these gaps through a Governance-Capability-Digitalization (GCD) framework and proposes a Strategic MSME Development Model integrating digital transformation, institutional accessibility, and continuous capacity-building. Implications extend to policy reform, MSME governance design, and sustainable local economic empowerment aligned with Islamic economic principles of maslahah and social justice.
Keywords: Local Government Role; MSME Development; Chip Industry; Digital Governance; Bandar Lampung; Islamic Economic Empowerment; Policy Analysis